Progress and application of functional magnetic resonance imaging in acute kidney injury - Liu Zi-yang; Luo Jing; Jiang Lei; Cao Hong-di (Linchuang shenzangbing zazhi)
Acute kidney injury （AKI） is a globally highly prevalent clinical syndrome characterized by a sudden deterioration of renal function. It occurs in a variety of clinical conditions and its severity is closely associated with increased subsequent mortality， poor prognosis， and chronicity of renal injury. Therefore， an early recognition of AKI and timely interventions are crucial. Currently， there are limited clinical diagnostic techniques for AKI， and there lacks sufficiently sensitive and widely available monitoring methods. Functional magnetic resonance imaging （fMRI） is an increasingly powerful imaging modality， including blood oxygenation level dependent （BOLD）， arterial spin labeling （ASL）， diffusion weighted imaging （DWI）， intravoxel incoherent motion （IVIM）， diffusion kurtosis imaging （DKI）， diffusion tensor imaging （DTI）， and T1 mapping， T2 mapping， etc. These techniques can non-invasively assess renal oxygenation and perfusion， and reflect the changes in renal microstructure， providing the potential to detect AKI and predict the long-term outcome of AKI. This review summarized the recent studies of fMRI in AKI and provides a reference for future clinical applications.